Electrical resistivity of bulk multi-walled carbon nanotubes synthesized by an infusion chemical vapor deposition method - P. Singjai (2018)
Multi-walled carbon nanotubes (MWNTs) were synthesized by infusing alcohol into a tube furnace. A nickel catalyst preparation was made by a reduction reaction of NiO powder by ethanol vapor at 450 °C for 30 min before the MWNT synthesis at 700 °C for 1-18 h. The as-grown MWNTs were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction and Raman spectroscopy. Large quantities of MWNTs, having a diameter in the range of 20-50 nm can be produced from ethanol vapor without a carrier gas by this technique. A method to measure an electrical resistance of bulk MWNTs was carried out under stress between two conducting plates. The result shows an exponentially correlation between the resistivity and the D-band/G-band intensity ratio, suggesting that the measuring method provides a simple tool to monitor the degree of structural defects of MWNTs. © 2006 Elsevier B.V. All rights reserved.